A stitch in time saves nine: external quality assessment rounds demonstrate improved quality of biomarker analysis in lung cancer - Keppens, Cleo; Tack, Véronique; Hart, Nils 't; Tembuyser, Lien; Ryska, Ales; Pauwels, Patrick; Zwaenepoel, Karen; Schuuring, Ed; Cabillic, Florian; Tornillo, Luigi; Warth, Arne; Weichert, Wilko; et al. (Oncotarget, 2018)
Biomarker analysis has become routine practice in the treatment of non-small cell lung cancer (NSCLC). To ensure high quality testing, participation to external quality assessment (EQA) schemes is essential. This article provides a longitudinal overview of the EQA performance for EGFR, ALK, and ROS1 analyses in NSCLC between 2012 and 2015. The four scheme years were organized by the European Society of Pathology according to the ISO 17043 standard. Participants were asked to analyze the provided tissue using their routine procedures. Analysis scores improved for individual laboratories upon participation to more EQA schemes, except for ROS1 immunohistochemistry (IHC). For EGFR analysis, scheme error rates were 18.8%, 14.1% and 7.5% in 2013, 2014 and 2015 respectively. For ALK testing, error rates decreased between 2012 and 2015 by 5.2%, 3.2% and 11.8% for the fluorescence in situ hybridization (FISH), FISH digital, and IHC subschemes, respectively. In contrast, for ROS1 error rates increased between 2014 and 2015 for FISH and IHC by 3.2% and 9.3%. Technical failures decreased over the years for all three markers. Results show that EQA contributes to an ameliorated performance for most predictive biomarkers in NSCLC. Room for improvement is still present, especially for ROS1 analysis.
Keywords: targeted therapy; biomarker analysis; external quality assessment; molecular pathology; non-small cell lung cancer